Nepal Himalaya, Bericht einer Reise nach Ostnepal im Jahre 1963 - Haffner, Willibald (ERDKUNDE, 1965)
Since the Kingdom of Nepal opened its boundaries in 1951, a considerable number of expeditions have carried out research in the country. Under the auspices of the Ger man Research Scheme of Nepal seven research teams have spent some time in the eastern part of the Kingdom. The 6th work team, which travelled in Nepal in 1963, consisted of two meteorologists, H. Kraus and K. Hackl, a doctor, F. Zimmer, and a geographer, W. Haffner. The purpose of the meteorological investigations was to measure and determine the insolation and radiation regimes in the subtropical high mountain area, while the geographical work was concerned with the altitudinal composition of landscapes in eastern Nepal. From a large scale point of view Nepal exhibits in cross section a clearly expressed fourfold division: the Terai, an area still belonging to the Himalayan Foreland, followed by the Sivalik chains, the outer Himalayan ranges, and finally the main Himalayan ranges. The vegetation profile extends from tropical sal-forests into the zone of alpine meadows and steppes. The most favourable zone for non-irrigated argriculture lies between 1,500 and 2,850 metres; agriculture can continue there even in winter. In the habitats of the ethnical groups of eastern Nepal a vertical sequence is also discernible. The level of the low valleys is inhabited by Indo-Aryans who immigrated from India. The high valleys are settled by Mongolian peoples who came here from the North, from Tibet. The zone of intermediate altitude appears to be the retreat area of population groups indigenous to Nepal - Nevar, Tamang, Rai, Limbu. Between one valley and the next there is frequently a change in the kind of land use, of settlement, of village and house types, of religion and songs, of languages and traditional customs, of the entire way of life and, as a result, the appearance of the landscape also changes.